The Problem of Trust. Victories and Retreats - Kavolis, Vytautas (Sociologija. Mintis ir veiksmas, 1997)
The article presents a lecture that was read in Santara-Šviesa conference in Vilnius-Anykščiai (1996 July 20-23). A shortened version of the lecture was published in a journal Kultūros Barai (1996/8-9).